Perceptions of clinical athletic trainers on the spiritual care of injured athletes - McKnight, C. M.; Juillerat, S. (Journal of Athletic Training, 2011)
Context: Treating both the body and the mind of an injured or ill patient is accepted as necessary for full healing to occur. However, treating the spiritual needs of the patient has less consensus.